Experimental and computational evidence for KOt-Bu-promoted synthesis of oxopyrazino[1, 2-a]indoles. Issue 123 (24th November 2015) - Mahdavi, Mohammad; Hassanzadeh-Soureshjan, Rasoul; Saeedi, Mina; Ariafard, Alireza; BabaAhmadi, Rasool; Ranjbar, Parviz Rashidi; Shafiee, Abbas
Abstract : Metal-free intramolecular hydroamination of some Ugi adducts in the presence of KO t -Bu in DMF at room temperature led to the formation of novel oxopyrazino[1, 2- a ]indole derivatives. Abstract : A novel series of oxopyrazino[1, 2- a ]indole derivatives were prepared via a two-step synthetic procedure including a Ugi-four-component reaction followed by the transition metal-free intramolecular hydroamination of Ugi adducts in the presence of KO t -Bu in DMF at room temperature. Density functional theory (DFT) calculations were also performed to elucidate the mechanistic aspects of the reaction.